Response Of Liquid Organic Fertilizer Concentration Levels on The Growth and Yield of Three Varieties of Pakchoy (Brassica rapa L.) - Seftiani, Rani; Laila, Alfu; Rumbiak, Julio Eiffelt Rossaffelt; Sulistyorini , Endang (Sam Ratulangi University, 2026)
Pakchoy production in Indonesia has declined due to excessive use of inorganic fertilizers and suboptimal cultivation practices, necessitating the adoption of alternative fertilization methods, such as liquid organic fertilizer (LOF), which can improve soil structure, provide readily available nutrients, and enhance plant growth. This study aimed to determine the effects of varying concentrations of Infarm LOF on the growth and yield of three pakchoy (Brassica rapa L.) varieties to identify the most effective combination for cultivation. The Research was conducted from September to November 2025 in the home yard area of Kp. Cibuah, Cibuah Village, Warunggunung District, Lebak Regency, Banten, using a randomized block design with two factors: LOF concentration and pakchoy varieties. LOF concentration levels were P0 (no LOF), P1 (3 mL/L), P2 (6 mL/L), and P3 (9 mL/L), while varieties included (V1 = Nauli F1, V2 = Flamingo, and V3 = Green). The results showed that P1 (3 mL/L) produced the best growth performance, indicated by plant height and fresh shoot weight. The Nauli F1 variety showed the best growth response across most parameters. In addition, a significant interaction between Infarm LOF concentration and pakchoy varieties was observed for leaf number and leaf greenness. Keywords: Infarm, Pakchoy, Concentration level, Variety